Kemampuan Berpikir Kritis pada Model Project Based Learning disertai STEM Siswa SMA pada Suhu dan Kalor - Sumardiana Sumardiana; Arif Hidayat; Parno Parno (Graduate School of Universitas Negeri Malang, 2019)
Abstract: Critical thinking skills can be grown with learning project based learning models. The purpose of this study was to analyze Critical Thinking abilities with project-based learning (PjBL) students at temperature and heat at the high school level. This research was conducted at SMAN 2 Batu class XI. The subjects of this study were 35 students. This type of research is a mixed method embedded in experimental models. With a test of critical thinking skills the essay forms as many as 8 items. The results showed that there were differences in critical thinking of students before and later getting PjBL training on the material heat and temperature. The result of the research showed that students’ critical thinking has increas.Abstrak: Keterampilan berpikir kritis dapat ditumbuhkan dengan model pembelajaran project based learning. Tujuan penelitian ini adalah untuk menganalisis kemampuan berpikir kritis dengan project based learning (PjBL) siswa pada suhu dan kalor pada tingkat SMA. Penelitian ini dilakukan di SMAN 2 Batu kelas XI. Subjek penelitian ini berjumlah 35 siswa. Jenis penelitian ini Mixed method embedded experimental model. Dengan test kemampuan berpikir kritis berbentuk essay sebanyak delapan butir. Hasil penelitian menunjukkan bahwa terdapat perbedaan keterampilan berpikir kritis siswa sebelum dan sesudah mendapatkan perlakuan PjBL pada materi suhu dan kalor. Kemampuan berpikir kritis siswa mengalami peningkatan pada setiap indikator.